Software HIDROKSI Development to Detect and Reduce Misconceptions Using Conceptual Change Text Strategy on Salt Hydrolysis - Alvira Dwi Yanti; Sukarmin Sukarmin (International Journal of Chemistry Education Research, 2021)
This research aims to determine the feasibility of software HIDROKSI to detect and reduce students' misconceptions using a conceptual change text strategy on salt hydrolysis. This research used the Research & Development (R&D) method with 3rd grade SMAN 1 Krian’s student as a subject. The instruments used are student response questionnaires and student activity observations. Software HIDROKSI was developed using the Adobe Flash CS6 Action Script 3.0. The results analyzed using the quantitative descriptive method are as follows: (1) Software HIDROKSI isvalid with an average percentage of content validation is 86.67% and construct validation is 86.22% (2) The practicability of software HIDROKSI is very practical with an average percentage of student response questionnaire results is 96.61% (3) The effectiveness of software HIDROKSI in detecting and reducing student’s misconceptions is very effective with an average percentage of students' shift in conceptions from misconceptions to knowing concepts is 86.34%.